Ion Transport and Reordering in a 2D Trap Array. Issue 11 (19th May 2020) - Wan, Yong; Jördens, Robert; Erickson, Stephen D.; Wu, Jenny J.; Bowler, Ryan; Tan, Ting Rei; Hou, Pan‐Yu; Wineland, David J.; Wilson, Andrew C.; Leibfried, Dietrich
Abstract: Scaling quantum information processors is a challenging task, requiring manipulation of a large number of qubits with high fidelity and a high degree of connectivity. For trapped ions, this can be realized in a 2D array of interconnected traps in which ions are separated, transported, and recombined to carry out quantum operations on small subsets of ions. Here, functionality of a junction connecting orthogonal linear segments in a 2D trap array to reorder a two‐ion crystal is demonstrated. The secular motion of the ions experiences low energy gain and the internal qubit levels maintain coherence during the reordering process, therefore demonstrating a promising method for providing all‐to‐all connectivity in a large‐scale, 2D or 3D trapped‐ion quantum information processor. Abstract : Scaling quantum information processors is a challenging task, requiring manipulation of many qubits with high fidelity and a high degree of connectivity. For trapped ions, this can be realized in a 2D array of interconnected traps. Here, functionality of a junction connecting two straight linear trap sections to reconfigure a two‐ion crystal is demonstrated, representing a promising method for enhancing connectivity.